Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Yayasan Al-Fityan School Tangerang - Aliyah Putri, Zahra; Ananta Vidada, Irwin (Economic Reviews Journal, 2025)
This study aims to determine the influence of work motivation and work discipline on employee performance at the Al-Fityan School Foundation, Tangerang. The study used a quantitative approach with a survey method. The research sample was 64 respondents taken using a simple random sampling technique from a population of 178 employees. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, f-tests, and determination coefficients. The results showed that work motivation and work discipline partially and simultaneously had a significant effect on employee performance. This study concludes that increasing work motivation and discipline can be an effective strategy to improve employee performance in educational institutions.